Larangan Menggandakan Dokumen Jabatan Pejabat Pembuat Akta Tanah (PPAT) Bagi Calon PPAT yang Menjalani Magang - Ari Dwiatmika, Anak Agung Ngurah (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 4 No 1 (2019), 2019)
Land Deed Official (LDO) candidates who undergo an internship are prohibited from copying LDO’s documents in accordance with Article 9 paragraph (3) Regulations of the State Minister of Agrarian Affairs number 10 of 2017, but the arrangement is unclear because it is not specified only applies from copying documents without permission or also applies against copying document with permission. The obscurity of the rule raises doubt for LDO candidates who undergo an internship to assist when asked for assist by LDO to copy LDO’s documents to be used as supplementary files for deed registration. The problems discussed in this research are how the scope of the LDO’s documents are prohibited from being copied by the LDO candidates who undergo an internship and whether copying the LDO’s documents at the LDO’s request carried out the infringement of law. The purposes of the study are to find out the scope of the documents that banned to copy and to find out copying the LDO’s documents at the LDO’s request is an infringement or not. The research used normative legal research method. The conclusion are the scope of the LDO’s documents which is prohibited from being copied includes the paper based documents and electronic documents used by LDO to carry out his position, as well as the draft deeds and draft letters which have not been signed. Copying the LDO’s documents based on the request of the LDO or with permission from the LDO for office needs is not an infringement. Calon Pejabat Pembuat Akta Tanah (PPAT) yang menjalani magang dilarang menggandakan dokumen pelaksanaan jabatan PPAT sesuai Pasal 9 ayat (3) Permen Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 10 Tahun 2017, namun pengaturan pada pasal tersebut tidak jelas karena tidak ditentukan larangan tersebut hanya berlaku terhadap penggandaan dokumen tanpa izin dari PPAT atau berlaku juga terhadap penggandaan dokumen atas izin PPAT. Ketidakjelasan aturan tersebut menimbulkan keragu-raguan bagi calon PPAT yang menjalani magang untuk membantu ketika dimintai bantuan oleh PPAT untuk menggandakan atau memfotokopi dokumen jabatan PPAT untuk digunakan sebagai berkas pelengkap pendaftaran akta. Permasalahan yang diteliti adalah bagaimana ruang lingkup dokumen pelaksanaan jabatan PPAT yang dilarang digandakan oleh calon PPAT yang menjalani magang, dan apakah perbuatan menggandakan dokumen pelaksanaan jabatan PPAT yang dilakukan atas permintaan PPAT termasuk perbuatan melanggar hukum. Tujuan penelitian untuk mengetahui ruang lingkup dokumen yang tidak boleh digandakan dan untuk mengetahui perbuatan menggandakan dokumen pelaksanaan jabatan PPAT atas permintaan PPAT merupakan pelanggaran atau tidak. Metode yang digunakan adalah penelitian hukum normatif. Kesimpulannya ruang lingkup dokumen pelaksanaan jabatan PPAT yang dilarang digandakan meliputi dokumen fisik dan dokumen elektronik yang digunakan PPAT melaksanakan jabatannya, serta draf akta dan draf surat-surat yang belum ditanda tangani. Menggandakan dokumen pelaksanaan jabatan PPAT atas permintaan PPAT atau atas izin PPAT untuk keperluan kantor PPAT bukan tindakan pelanggaran.